A Study on Prevention of Soil Erosion in Hilly Region Using Jute Footrub Mats (International Journal of Innovative Research in Computer Science & Technology, 2022)
Topsoil erosion is the most common  issues in today’s world related to soil distresses. Soil  erosion can cause contamination of drinking water,  disturbs ecosystem of lakes and other water bodies and can  cause landslides problems in hilly regions. It becomes necessary to prevent soil erosion by using some methods.  This project discusses to prevent soil erosion by using jute  mats or jute sacks in hilly regions. For this project work we  have choose the nearby hill of Bhimber Gali which has  experienced landslide in recent days. After that, we have  to prepare the box model of dimensions  150cm*50cm*40cm to show all the site properties such as  field density, moisture content etc. in physical modeling.  Moreover, it is needed to measure slope inclination of the  hill by help of theodolite surveying and prepare same slope  in box model. Then, rainfall data analysis is necessary for  simulation of rainfall in laboratory for this we have to take  rainfall data of Poonch district of J&K for last 5 years.  Further then, scaling of model dimensions and rainfall data  is done accordance with the need. Then simulation of  rainfall must be done in laboratory by calibrating  according to the scaling value of rainfall intensity and  simulation of rainfall must be done by applying jute mats and steel fence as well as without applying them. After  simulation of rainfall we have to measure soil erosion by  the help of runoff collector method as well as we have to  examine the slope changes and slope failure, if happen.  Further then, if slope failure of box model not take place  by applying jute mats then examine the slope changes or  failure at different intensities greater than given district  rainfall intensity.
Keywords: Water Content; Field Density; Shear Strength; Rainfall Intensity; Displacement; Jute; Footrub Mats